THE LITERARY LEGACY OF BABUR: A COMPARATIVE STUDY OF THE BABURNAMA’S TRANSLATIONS - Dusboyev Abdurashid Abdug'opir og'li (Bright Mind Publishing, 2025)
The Baburnama, the autobiography of Zahir-ud-Din Muhammad Babur, founder of the Mughal Empire, is a seminal work in Islamic, Central Asian, and South Asian literature. Originally written in Chagatai Turkic, the Baburnama offers insights into Babur’s military campaigns, reflections, and cultural milieu. This study examines the literary legacy of Babur through a comparative analysis of major translations—especially Persian and English versions—highlighting how linguistic, stylistic, and interpretive choices have influenced its reception across time and cultures.
Keywords: Translation, memoir, translation variation, Baburnama, poetry, legacy.